Labour of love or labour of pain? Understanding and navigating the precarity of media freelancing in Singapore - Yip, Timothy (Nanyang Technological University, 2023)
Media work is becoming increasingly precarious due to changing work and labour arrangements. Furthermore, the degree of precarity faced is hard to universalise as it is highly dependent on social, political, and demographical factors. Therefore, this study aims to contribute to the current state of research around media freelancers in Singapore and the types of precarity impacting them by understanding the social forces acting, creating and influencing such precarity, and how they navigate it. Using 11 semi-structured interviews with media freelancers, I find that Singapore media freelancers struggle with pricing, competition, a lack of protection and benefits, and that they continue to face precarity despite Singapore having support mechanisms to address it. I also find that media freelancers rely on informal networks and centralising in collectives to mitigate precarity. Further research needs to understand the attitudes and approaches of these freelancers and why they do not use such support.